1995
DOI: 10.1080/00140139508925111
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical risk factors for occupationally related low back disorders

Abstract: A continuing challenge for ergonomists has been to determine quantitatively the types of trunk motion and how much trunk motion contributes to the risk of occupationally-related low back disorder (LBD). It has been difficult to include this motion information in workplace assessments since the speed at which trunk motion becomes dangerous has not been determined. An in vivo study was performed to assess the contribution of three-dimensional dynamic trunk motions to the risk of LBD during occupational lifting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
286
1
8

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 546 publications
(300 citation statements)
references
References 84 publications
5
286
1
8
Order By: Relevance
“…Performance of repetitive activities, such as bending and twisting, is a known risk factor for LBP. 2,15,18,23,24,26 Principles of the physical stress theory also would suggest that an increase in frequency of movement of a specific region across the day may contribute to increased stress on biological tissues, leading to injury and eventually pain. 21 Although data suggest that people with LBP display early lumbopelvic movement with various clinical tests, 6,9,33,36 currently the factors contributing to the early movement are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of repetitive activities, such as bending and twisting, is a known risk factor for LBP. 2,15,18,23,24,26 Principles of the physical stress theory also would suggest that an increase in frequency of movement of a specific region across the day may contribute to increased stress on biological tissues, leading to injury and eventually pain. 21 Although data suggest that people with LBP display early lumbopelvic movement with various clinical tests, 6,9,33,36 currently the factors contributing to the early movement are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can be aggregated into a smaller number of categories [9] including biomechanical factors (regular lifting, exposure to vibration, physically demanding jobs, bending and twisting, pushing and pulling heavy loads, awkward posture) [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20], psychological/psychosocial factors (job satisfaction, local support in the workplace, depression, job control, stress) [2,7,9,16,[19][20][21][22][23][24][25] and individual risk factors (sedentary lifestyle, age, smoking, gender, obesity, poor general health, marital status, pregnancy) [2,7,9,12,13,20,21,23,[26][27][28][29][30][31]. Past studies have investigated many of these factors and their relationship to LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have focused on biomechanical hypotheses to explain the association between sitting and LBP [45,47,56,74,80]. The literature on this subject is extensive, but the evidence is somewhat contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent investigation, Wilke et al [80] reevaluated the intradiscal pressure in sitting and found that, in fact, it can be lower in sitting than in erect standing. Another hypothesis is that prolonged static sitting postures may have a negative effect on the nutrition of the intervertebral disc [47]. Thus, a constantly changing position may promote the flow of fluid (nutrition) to the disc [75].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation